Contextual factors matter: A two-year exploration into the impact of contextual factors on elite women’s rugby sevens match-play movement demands - Ross J. Brosnan; Denis Visentin; Greig Watson; Matthew Schmidt (PLoS ONE, 2025)
Introduction and aims Women’s rugby sevens is a rapidly growing sport that imposes unique match-play movement demands on participants. This research investigated the effect of contextual factors on the match-play movement demands of international and domestic women’s rugby sevens players. Methods An observational, longitudinal study design was conducted to characterise Global Navigation Satellite Systems (GNSS) match-play movement demands in international (n = 23) and domestic (n = 42) players across two seasons and nine series of an elite domestic women’s dual-level rugby sevens tournament. In total, across the 65 players, 1461 matches were analysed. Match-play movement demands were assessed through distance, speed, and acceleration metrics using 10 and 15 Hz (5 Hz interpolated to 15 Hz) GNSS devices. Contextual factors were grouped into four themes: Player, Match, Tournament, and Environment. Data was analysed using univariate and multivariate mixed-effects regression. Results Multi-variate regression identified that higher intensity match-play movement demands were associated with day 1, half 1, winning and/or drawing the match, closer score lines, playing in a top-5 ranked team, playing against opponents closer in the standings, starting the match, playing as a back or speed edge, being an international player, playing in warmer climates, and playing later in the day. Conclusion This study highlights how contextual factors can affect match-play movement demands in women’s rugby sevens. These findings can help coaches tailor training, optimise tactical decisions, and manage player workloads more effectively.